Pelatihan Membuat Media Pembelajaran Berbasis Internet - Mahendra Adhi Nugroho (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Teachers often overlook the importance of learning media in supporting the learning process for various reasons. These include the limited preparation time, difficulty finding suitable media, and unavailability of sufficient funds. The purpose of the training is to introduce the use of learning media that can be an alternative for teachers and can be implemented in the learning process. The training aims to help create internet-based learning media with android applications and web blogs in the classroom learning process for MGMP teachers in the Accounting Skills Program in Sleman Regency. At the end of the activity, participants felt that the training activity was beneficial for developing we-blog-based learning media and android applications that they would use in learning at their respective schools. Participants' responses to the training activities carried out stated that from the quality of the presenters, the quality of the modules was excellent.